New Insights into Toxicity and Drug Testing - Gowder, Sivakumar (IntechOpen, 2013)
This book "New Insights into Toxicity and Drug Testing" covers all emerging technologies (profiling technologies, 3D cultures, next generation sequencing etc.), available methods and models to evaluate candidate drugs and medicinal plants with reference to toxicity, drug testing and development. This book is an original contribution of experts from different parts of the globe and the in-depth information will be a significant resource for scientists and physicians who are directly dealing with drugs / medicines and human life.